Implementasi Kewarganegaraan Dalam Taat Negara Indonesia: Tinjauan Terhadap Undang-Undang Kewarganegaraan No.12 Tahun 2006 (International Forum of Researchers and Lecturers, 2024)
Law No. 12 of 2006 on Indonesian Citizenship is a significant step in citizenship law reform, responding to the challenges of globalization and international mobility. This law adopts the jus sanguinis principle as the basis for determining citizenship, with limited application of jus soli to prevent statelessness. Children born from mixed marriages between Indonesian and foreign nationals are allowed dual citizenship until they reach the age of 18. This study aims to analyze the implementation of Law No. 12 of 2006 in the contemporary social and political context, and to identify the challenges that arise in its application. The research employs qualitative analysis and literature reviews from academic journals and empirical data. The findings reveal challenges such as complex bureaucratic procedures, lack of public awareness of citizenship rights and obligations, and inadequate protection for Indonesian citizens abroad. It is recommended that administrative procedures be simplified through digitalization, citizenship education be enhanced, and the protection of Indonesian citizens overseas be strengthened. These improvements are expected to enable the law to be implemented more effectively and to better respond to the needs of Indonesian citizens in the global era.